Partial Rank, Linear Management Information System's. - Dietrich, Richard; Weil, Roman L. (The Accounting Review, 1974)
This article reports that any set of business accounting statements implies a redundant set of linear equations that specifies the interactions in that business. That is, from a set of accounting statements, one can construct a system of linear equations. In order to understand the underlying business, it appears useful to construct that linear system to specify relations that make the system one of full rank, and to solve it. Management can be expected to learn about the number of degrees of freedom it has in setting goals or parameters for its business, or financial statements, the relations between various possible sets of independent decisions, and the effects of possible future actions. Economists have prepared a series of interactive computer programs that will facilitate the kind of analysis about to be described. These flows show the Gross National Product for the U.S. economy for 1972. These data have been condensed from more detailed national income accounts. Implied by the data underlying these statements are a flow of funds and a system of equations.